A sign of affection. 5 - Dashiell, Christine, 1984-; Vanstiphout, Carl; Blakeslee, Lys, 1985- (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2022)
Yuki is a typical college student--it's just that she can't hear. A chance encounter on a train leads to a serious crush... but will he give her a chance? Yuki's life revolved around friends, fashion, her classes, and social media, until something interrupted her routine: a chance meeting with Itsuomi, a classmate with a passion for languages, world travel, movies--and, increasingly, for Yuki. Amazed at how casually Itsuomi asked her out, Yuki couldn't help but wonder how serious this relationship was for him, but, with Itsuomi showing his devotion in little ways, every day, another thrilling thought has entered her mind: What if this new happiness could become her new normal?